Search for Anti-EA(D) Antibodies in Subjects with an “Isolated VCA IgG” Pattern - Massimo De Paschale; Debora Cagnin; Teresa Cerulli; Maria Teresa Manco; Carlo Agrappi; Paola Mirri; Arianna Gatti; Cristina Rescaldani; Pierangelo Clerici (International Journal of Microbiology)
The presence of an “isolated viral capsid antigen (VCA) IgG” pattern in serum is not easy to interpret without the aid of further tests, such as specific immunoblotting or a virus genome search, that often give rise to organisational and economic problems. However, one alternative is to use an enzyme-linked immunosorbent assay (ELISA) to detect anti-early antigen (EA) antibodies, which can be found in about 85% of subjects with acute Epstein-Barr virus (EBV) infections. The purpose of this work was to search for anti-EA(D) antibodies in 130 samples with an isolated VCA IgG pattern at ELISA screening and classified as being indicative of past (102 cases) or acute (28 cases) infection on the basis of the immunoblotting results. Thirty-seven samples (28.5%) were positive for anti-EA(D), of which 25 (89.3%) had been classified by immunoblotting as indicating acute and 12 (11.8%) past EBV infection. This difference was statistically significant (𝑃<.01). The results of our search for anti-EA(D) antibodies correctly identified nearly 90% of acute (presence) or past EBV infections (absence). When other tests are not available, the search for anti-EA antibodies may therefore be helpful in diagnosing patients with an isolated VCA IgG pattern at screening tests.